PENGARUH PENGGUNAAN MEDIA VIDEO PEMBELAJARAN UNTUK MEREDUKSI MISKONSEPSI MATEMATIKA SISWA - Yandi Heryandi; Nur`aini Nur`aini (Integral : Pendidikan Matematika, 2022)
ABSTRACT This study aims to: (1) determine students' mathematical misconceptions (2) determine student responses to instructional video media (3) determine the effect of using instructional video media to reduce students' mathematical misconceptions. This type of research is a mixed study with a one group pre-test post-test design. Subjects are students of class X-B MA Addzikro Putat Payung for the 2020/2021 academic year. The instrument used is a questionnaire and a CRI (Certainty of Response Index) test. The results showed: (1) the average percentage of pre-test and post-test data was 57.4% and 13.4% so that it was reduced by 44%, meaning that there was a reduction in misconceptions (2) the student response questionnaire showed a positive response, the average percentage is 74% with good category. (3) the data on the linear regression test shows the value of Sig. 0.000 <0.05 then Ha is accepted and H0 is rejected. From the value of R Square in the determination test 0.659 or 65.9% with a strong category while 34.1% is the magnitude of the influence of other factors, meaning that there is a significant influence and there is a strong contribution in the use of learning video media to reduce students' mathematical misconceptions. Keywords: Learning Video Media, Misconceptions, CRI ABSTRAK Penelitian ini bertujuan untuk: (1) mengetahui miskonsepsi matematika siswa (2) mengetahui respon siswa terhadap media video pembelajaran (3) mengetahui pengaruh penggunaan media video pembelajaran untuk mereduksi miskonsepsi matematika siswa. Jenis penelitian ini penelitian campuran dengan desain one group pre-test post-test design. Subyek siswa kelas X-B MA Addzikro Putat Payung tahun ajaran 2020/2021. Instrumen yang digunakan adalah angket dan tes CRI (Certainty of Response Index). Hasil penelitian menunjukkan: (1) rata-rata persentase data pre-test dan post-test adalah 57,4% dan 13,4% sehingga berkurang sebesar 44%, artinya menunjukkan adanya pengurangan miskonsepsi (2) angket respon siswa menunjukkan respon positif, persentase rata-rata 74% dengan kategori baik. (3) data pada uji regresi linear menunjukkan nilai Sig. 0,000<0,05 maka Ha diterima dan H0 ditolak. Dari nilai R Square pada uji determinasi 0,659 atau 65,9% dengan kategori kuat sedangkan 34,1% adalah besarnya pengaruh faktor lain, artinya terdapat pengaruh signifikan dan terdapat kontribusi kuat dalam penggunaan media video pembelajaran untuk mereduksi miskonsepsi matematika siswa. Kata kunci: Media Video Pembelajara, Miskonsepsi, CRI